Implikasi Hukum Terhadap Kredit Bermasalah Pada Perusahaan Pembiayaan Saat Wabah Pandemi Covid 19 (Universitas Suryakancana, 2022)
In the era of the Covid-19 Pandemic as a form of national disaster that must receive special attention, because the condition of the Covid-19 Pandemic greatly affects the health and economy of the community. The community's economy as a result of the Covid-19 pandemic, has an impact on finance companies where debtors have difficulty in paying debt obligations. The implementation of the responsibilities of financial institutions as institutions that collect public funds in carrying out their activities is regulated in the Financial Services Authority regulation Number 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy. Basically, by providing asset quality determination and concessions to debtors by means of credit restructuring is the best step. Thus, debtors whose credit is bad because of problems cannot pay off debts can be saved. The title of this article is the legal implications of non-performing loans in financing companies as a forum for collecting public funds which will later be channeled back to people who need funds. The purpose of this research is expected to increase knowledge of scientific works in the field of financing law, and is also expected to contribute ideas in terms of scientific development, especially in financing law.Keywords : Legal Implications, Non-Performing Loans, Financing Companies, Covid 19 Pandemic.